Large-scale porphyry-type mineralization in the Central Asian metallogenic domain: A review. (1st October 2018) - Gao, Jun; Klemd, Reiner; Zhu, Mingtian; Wang, Xinshui; Li, Jilei; Wan, Bo; Xiao, Wenjiao; Zeng, Qingdong; Shen, Ping; Sun, Jinggui; Qin, Kezhang; Campos, Eduardo
Graphical abstract: Highlights: The CAMD is one of the most important porphyry-type deposit domains on earth. CAMD porphyry deposits are associated with the evolution of three Paleo-oceans. MASH and slab melting models can explain the genesis of some PCDs in the CAMD. A new model involves 'enriched lower crust and relictic oceanic ridge subduction' Melting of juvenile lower crust was essential for Mo mineralization. Abstract: A series of porphyry-type Cu-(Mo)-(Au) deposits including some giant world-class deposits such as Kounrad, Aktogai, Kal'makyr, Oyu Tolgoi and Chalukou occur in the Central Asian metallogenic domain (CAMD). The outline of the CAMD almost overlaps with that of the Central Asian orogenic belt (CAOB), which is located between the East Europe, Siberia, Tarim and North China cratons. The CAMD comprises sparsely exposed tectonic slices of Precambrian high-grade metamorphic basement rocks that are sandwiched between Phanerozoic accretionary complexes and arc rocks. According to geological, metallogenic, geochronological and tectonic setting characteristics, the CAMD comprises three metallogenic provinces: (1) the Kazakhstan Cu-Au-Mo, (2) the Mongolia Cu-Au and (3) the Northeast China Mo-Cu metallogenic provinces. Early Paleozoic (∼490 to 440 Ma) and Late Paleozoic (∼330 to 295 Ma) large scale porphyry-type mineralization in the Kazakhstan metallogenic province is intimately associated with the evolution of the Central Tianshan–Yili–Northern Tianshan–Kokchetav–Chingiz Paleozoic arc system which was terminated by the late Permian closure of the western segment of the Paleo-Asian Ocean. In contrast, the ∼370 Ma and ∼240 Ma porphyry-type mineralization of the Mongolia metallogenic province is related to the Tuva–Mongolia arc collage system that was formed during the evolution of the Paleo-Asian Ocean in the Paleozoic and the Mongol–Okhotsk Ocean in the early Mesozoic. Furthermore, the Northeast China metallogenic province was affected by three distinct geodynamic processes that were associated with the Paleo-Asian, Mongol–Okhotsk and Paleo-Pacific Oceans during the Paleozoic (>250 Ma), the early Mesozoic (>200 Ma) and the late Mesozoic (200–90 Ma), respectively. Except for the Early Paleozoic Cu mineralization at Duobaoshan (∼480 Ma) and Bainaimiao (440 Ma), the porphyry-type mineralization of this metallogenic province is predominantly characterized by widespread Mesozoic Mo mineralization. In general, porphyry-type deposits of the CAMD have geological, structural, metallogenic, alteration and fluid characteristics, which are consistent either with those related to the oceanic subductional arc settings of the Circum-Pacific metallogenic domain or with those of the continental collisional environment in the Tethyan metallogenic domain. The involvement of highly oxidized intermediate to felsic magmas is fundamental for the formation of porphyry deposits. Even though the prevalent MASH and slab melting models can be employed to interpret the genesis of some porphyry Cu deposits in the CAMD, a here newly suggested model, which is based on 'pre-enriched mafic lower crust and the subduction of a relictic mid-oceanic ridge', is thought to explain the large scale copper mineralization in the Balkhash–West Junggar metallogenic belt of the Kazakhstan metallogenic province. Nevertheless, most of the porphyritic suites associated with the Mo deposits in the Northeast China metallogenic province have relatively depleted mantle-like neodymium and hafnium isotopic compositions, suggesting that the ore-forming granitic magma may have predominantly been derived from juvenile lower crust. Upwelling of asthenosphere may have triggered the melting of the lower crust during post-collisional extension subsequent to the closure of the Paleo-Asian Ocean in the Triassic, the subduction of the Paleo-Pacific ocean in the Jurassic and the thinning of the lithosphere caused by rollback of the Paleo-Pacific plate in the Cretaceous. Ancient crustal components were only locally found to have been involved in the magma source of several medium-large Mo deposits.